Distinguishing Remobilized Ash From Erupted Volcanic Plumes Using Space‐Borne Multiangle Imaging. Issue 20 (30th October 2017) - Flower, Verity J. B.; Kahn, Ralph A.
Abstract: Volcanic systems are composed of a complex combination of ongoing eruptive activity and secondary hazards, such as remobilized ash plumes. Similarities in the visual characteristics of remobilized and erupted plumes, as imaged by satellite‐based remote sensing, complicate the accurate classification of these events. The stereo imaging capabilities of the Multiangle Imaging Spectroradiometer (MISR) were used to determine the altitude and distribution of suspended particles. Remobilized ash shows distinct dispersion, with particles distributed within ~1.5 km of the surface. Particle transport is consistently constrained by local topography, limiting dispersion pathways downwind. The MISR Research Aerosol retrieval algorithm was used to assess plume particle microphysical properties. Remobilized ash plumes displayed a dominance of large particles with consistent absorption and angularity properties, distinct from emitted plumes. The combination of vertical distribution, topographic control, and particle microphysical properties makes it possible to distinguish remobilized ash flows from eruptive plumes, globally. Key Points: A method for distinguishing remobilized ash from erupted volcanic plumes, using space‐borne vertical profiles, has been developed Microphysical particle analysis of remobilized ash found these plumes to be dominated by large nonabsorbing particles Remobilized ash plumes display uniform microphysical characteristics irrespective of the timing of the event or volcanic source